Correlación de las pruebas de susceptibilidad a la caries: recuento de estreptococos del grupo "mutans" y capacidad amortiguadora salivar en niños escolares de 9 a 11 años en Caldas, Antioquia, Colombia - Sierra, Luz Ines; Gaviria, Diana Maria; Alvarez, Patricia; Galeano, Maria Elena; Estrada, Maria del Socorro; Restrepo, Beatriz; Arbelaez, Maria Ines; Parra, Carlos Mario; Uscategui, Rosa (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The correlation betwwen the buffer cappacity, Streptoccocci of "mutans" group counts in saliva and caries (DFs index) in school children from Caldas, Antioquia, Colombia, between the age of 9 to 11 years old was taken. In spite of the population had shown Streptoccoccus of "mutans" group counts in saliva cultures (92.35%). Standar deviation was high: 368 x10^7 CFU/ml. Ten children between 0 and 1 x10^7CFU/ml and 9 children had between 1.000 and 3.000 x10^7 CFU/ml. Most of the population had high buffer capacity (mean 5.95) (Done by the final pH). Less than 25% was found to have buffer capacity lower than ´5 and the 25% had show a buffer capacity higher than 6.75. In boys the mean of buffer capacity was significantly higher (6.01) than the girls (5.44) p=0.007)). The DFs had shown a linear correlation with Streptoccocci of "mutans" group counts in salivar (r= 3.4 α=0.00) and a negaive correlation woth buffer cappacity (r= -0.19 α=0.00079). In the boys the association between Streptoccoccus of "mutans" group and DFs are similar to the group sample (r= 0.30 α=0.005) but in the girls are stronger (r= 0.67 α=0.0079). In the children with low caries (DFs less than 5) no association was found between the variables. In the group with more caries (DFs >19), DFs only had relation with Streptoccocci of "mutans"group (r= 0.435 α=0.0018). This group of high caries had als correlation between Streptoccocci of "mutans" group and oral higiene (r= 0.435 α=0.0018). In others parallels studies in the same population, Streptoccocci of "mutans group had shown a tendency of relation with sucrose intake.